2018
DOI: 10.1042/bsr20180511
|View full text |Cite
|
Sign up to set email alerts
|

Exploring major signaling cascades in melanomagenesis: a rationale route for targetted skin cancer therapy

Abstract: Although most melanoma cases may be treated by surgical intervention upon early diagnosis, a significant portion of patients can still be refractory, presenting low survival rates within 5 years after the discovery of the illness. As a hallmark, melanomas are highly prone to evolve into metastatic sites. Moreover, melanoma tumors are highly resistant to most available drug therapies and their incidence have increased over the years, therefore leading to public health concerns about the development of novel the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 315 publications
(413 reference statements)
1
18
0
Order By: Relevance
“…To solve this problem, a lot of researches are getting identification of the mechanisms by which melanoma initiation can be triggered and sustained. Recently, there are well known that melanoma may trigger not only the activation of RAS/MEK singling pathway, but also other pathways such as phosphoinositide 3-kinase (PI3K)/Akt and Wnt signaling pathways (57,58). In present study, we found that exposure to EEAD led to decrease protein expression of Akt and β-catenin in B16F10 cells (Supplementary Figure S1, http://www.…”
Section: Table 2 the Effects Of Oral Administration Of Eead To Ast supporting
confidence: 59%
“…To solve this problem, a lot of researches are getting identification of the mechanisms by which melanoma initiation can be triggered and sustained. Recently, there are well known that melanoma may trigger not only the activation of RAS/MEK singling pathway, but also other pathways such as phosphoinositide 3-kinase (PI3K)/Akt and Wnt signaling pathways (57,58). In present study, we found that exposure to EEAD led to decrease protein expression of Akt and β-catenin in B16F10 cells (Supplementary Figure S1, http://www.…”
Section: Table 2 the Effects Of Oral Administration Of Eead To Ast supporting
confidence: 59%
“…Approximately 2–3 million skin cancers cases are diagnosed each year and their incidence has increased over the last decades [207]. Skin tumors can be classified as non-melanomas (derived from keratinized epithelial cells) or melanomas (derived from melanocytes) [190,191].…”
Section: Impact Of Nlrs On Cancermentioning
confidence: 99%
“…Skin tumors can be classified as non-melanomas (derived from keratinized epithelial cells) or melanomas (derived from melanocytes) [190,191]. Melanoma accounts for 2% of the cases, being the most aggressive type of skin cancer, accounting for almost 10000 deaths per year [207,208].…”
Section: Impact Of Nlrs On Cancermentioning
confidence: 99%
“…Both the outgrowth of primary and metastatic melanoma pose significant and unprecedented clinical challenges. 1,2 Although surgical ablation is the most efficient treatment prior to melanoma invasion and the formation of metastases, a significant percentage of patients remains refractory. As a result, the five-year survival of patients is low, and malignant melanoma will become a formidable disease once cancer cells colonize other tissues.…”
Section: Introductionmentioning
confidence: 99%